Determinants of non-performing financing of Islamic rural banks in Indonesia - Lestari, Lutfi Bangun; Yeni, Ahmad Azhari Pohan; Ayu, Ayu Yuningsih (Economics, Finance, and Business Review, 2026)
This study analyzes the determinants of Non-Performing Financing (NPF) in Islamic Rural Banks (IRBs) in Indonesia by considering internal, external, and market competition factors. Internal variables include bank size (LAsset), Capital Adequacy Ratio (CAR), Cost to Income Ratio (CIR), and Financing to Deposit Ratio (FDR), while external variables include Gross Regional Domestic Product (GDP) and the impact of the COVID-19 pandemic. The Lerner Index is used as an indicator of market competition. Panel data from 154 IRBs for the 2019-2023 period was analyzed using a static panel. The results showed that the size of banks, CAR, CIR, and FDR had a significant influence on NPF, while the influence of market competition and macroeconomic conditions varied between Java and outside Java. These findings provide implications for IRB management in managing financing risks, for regulators in establishing policies that are responsive to different regional conditions, and enriching the empirical literature related to micro-Islamic banking. Further research is suggested to explore additional variables such as management quality, financing strategies, and local socio-economic factors to understand financing risk variations in more depth.